Lutte intégrée contre la mineuse de la tomate Tuta absoluta Meyrick (Lep. : Gelechiidae)  Dynamique des populations de T.absoluta sur tomate sous serre.  Efficacité de deux bio-insecticides. - Gacemi Abdelhamid (My University, 2011)
The work is a study on the tomato leafminer Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) which is the most important pest of tomato in Algeria. It causes spectacular damages since its introduction in 2008. The control against this invasive insect requires for several methods of control that complete the integrated control should solve the problem. The experimental work focused on dynamics of the populations of T.absoluta on a tomato crop protected by plastic located in the experimental farm of the University of Mostaganem (Mazagran). Ground testing has shown the progressive level of infestation by T.absoluta from March to June in spite of insect-proof netting to protect the culture. Treatments performed on field with a bioinsecticide (Emamectin benzoate) showed high efficiency on larval stages (mortality up to 87%). In laboratory conditions, we compared between the efficacy of Emamectin benzoate and Spinosad another bioinsecticide against larval stages of T.absoluta. The results showed that Emamectin benzaote and Spinosad showed an effective efficacy on the larvae of T.absoluta. Emamectin caused mortality of all stages of larvae treated, while Spinosad killed more than 94% of population.
Keywords: Tomato, Tuta absoluta, bioinsecticide, Spinosad, Emamectin benzoate, Mortality, Efficiency.